Water-based acrylic finishing paint based on core-shell structure design and preparation method of water-based acrylic finishing paint
By using a core-shell structure design, water-based acrylic topcoat, combined with urea-formaldehyde resin microencapsulated repair agent and multi-layer structure, the shortcomings of traditional coatings in terms of hardness, toughness and self-healing properties are solved, achieving a coating effect with high efficiency self-healing and excellent performance.
Patent Information
- Application Number
- CN202511367587.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-10-28
- Estimated Expiration
- 2045-09-24
AI Technical Summary
Traditional waterborne acrylic coatings are insufficient in terms of hardness, toughness, chemical resistance, and special functions, making it difficult to meet the needs of high-performance applications. Furthermore, self-healing coatings have poor compatibility in waterborne acrylic systems, affecting storage stability and application leveling. Microcapsules cannot achieve precise positioning and efficient utilization.
The water-based acrylic topcoat with a core-shell structure design achieves self-healing ability and high hardness and high flexibility by introducing urea-formaldehyde resin microencapsulated repair agent into the core layer and combining a rigid core, flexible intermediate layer and functional shell triple structure. The repair agent is released when the microcapsules rupture at the cracks for automatic healing.
It achieves excellent adhesion, impact resistance and crack resistance of the coating under different temperature environments, with a self-healing efficiency of 85%-95%, a pencil hardness of H and above, a flame retardant rating of UL94 V-0, and a gloss retention rate of over 80% after 1000 hours of weathering, meeting the requirements of harsh environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of acrylic topcoat technology, specifically referring to a water-based acrylic topcoat based on a core-shell structure design and its preparation method. Background Technology
[0002] Waterborne acrylic resins, with their advantages of being environmentally friendly, non-toxic, having excellent weather resistance, and good gloss and color retention, have become one of the most important film-forming materials in the coatings industry, and are widely used in automobiles, construction, furniture, industrial protection, and other fields. However, traditional waterborne acrylic coatings still have shortcomings in terms of hardness, toughness, chemical resistance, and special functionalities, making it difficult to meet the increasingly demanding requirements for high-performance applications.
[0003] To overcome these limitations, core-shell emulsion polymerization technology has been introduced into the development of waterborne acrylic coatings. This technology can effectively reconcile the contradiction between coating hardness and toughness by designing core and shell structures with different glass transition temperatures (Tg). However, a single core-shell structure can often only achieve performance improvement in one aspect and is difficult to integrate multiple advanced functions at the same time, such as long-lasting flame retardancy and self-healing. Moreover, its improvement in toughness is still insufficient in extreme low-temperature environments.
[0004] On the other hand, coatings inevitably suffer microscopic damage such as microscratches and microcracks during service. These damages become channels for water, oxygen, and corrosive ions to penetrate, leading to a sharp decline in the coating's protective performance and ultimately causing corrosion or aging of the substrate. To address this issue, the concept of self-healing coatings has emerged. Current research focuses on achieving self-healing functionality by adding microcapsules to the outer coating. However, directly applying this technology to waterborne acrylic systems faces significant challenges: First, physical blending with microcapsules severely disrupts the continuity and mechanical properties of the coating, leading to a decline in original performance; second, microcapsules have poor compatibility with waterborne acrylic emulsions, easily causing aggregation and sedimentation, affecting storage stability and application leveling; finally, simple physical blending cannot achieve precise positioning and efficient utilization of the repair agent, resulting in limited repair efficiency. Summary of the Invention
[0005] To overcome some of the problems mentioned in the background above, the present invention provides a water-based acrylic topcoat based on a core-shell structure design and its preparation method, so as to at least partially solve the above problems.
[0006] According to the technical solution of the present invention, a water-based acrylic topcoat based on a core-shell structure design is provided. The water-based acrylic topcoat comprises a water-based acrylic emulsion, which includes a core layer, an intermediate layer, a shell layer, additives, and the remainder water. Each component comprises, by mass, the following: Core layer: 20-30 parts methyl methacrylate, 10-20 parts butyl acrylate, 3-7 parts hydroxyethyl acrylate, and 2-4 parts vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 8-12 parts caprolactone-modified acrylic acid, 6-10 parts styrene, and 4-6 parts microencapsulated repair agent; Shell: 10-14 parts of fluorinated acrylate, 0.3-0.7 parts of light inhibitor and 1-3 parts of KH570 modified nano-silica; Additives: 1-2 parts emulsifier, 0.4-0.8 parts potassium persulfate, and ammonia water; The ammonia solution is used to adjust the pH of the topcoat to 7-8. The microencapsulated repair agent uses urea-formaldehyde resin as the wall material and encapsulates isocyanate compounds as the repair agent.
[0007] Preferably, the microencapsulated repair agent has a particle size of 1-5 μm, and the emulsifier includes the reactive emulsifier COPS-1.
[0008] On the other hand, the present invention also provides a method for preparing a water-based acrylic topcoat based on a core-shell structure design, comprising the following steps: Deionized water, emulsifier and methacrylic acid were added to the reaction vessel, heated and stirred, and then methyl methacrylate, butyl acrylate, hydroxyethyl acrylate and vinyltriphenyl dipentyl glycol phosphoramide mixed monomers were added for emulsification and then heated again. Potassium persulfate initiator solution was added dropwise to react and obtain core layer emulsion. A mixture of caprolactone-modified acrylic acid and styrene monomers and an initiator solution were simultaneously added dropwise to the core layer emulsion, and a microencapsulated repair agent was added slowly at the same time. After the addition was completed, the reaction was stirred to obtain an emulsion with an intermediate layer. Fluorinated acrylate, light inhibitor and KH570 modified nano-silica mixed monomer, initiator solution and emulsifier are added dropwise to the emulsion wrapped in the intermediate layer. After the addition is completed, the reaction is completed to obtain the shell-layer polymerized emulsion. After adding emulsifier and reacting, the pH is adjusted to 7-8 with ammonia water, and then filtered to obtain a core-shell structured aqueous acrylic emulsion. The core-shell structured waterborne acrylic emulsion is mixed and dispersed with pigments, fillers, thickeners, and defoamers to obtain a waterborne acrylic topcoat.
[0009] Further, deionized water, reactive emulsifier COPS-1, and methacrylic acid are added to the reaction vessel, heated to 60-65°C, and stirred for 35-45 minutes. Methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentyl glycol phosphoramide mixed monomers are added and emulsified for 30-40 minutes. The temperature is then raised to 80-85°C, and potassium persulfate initiator solution is added dropwise over 1-2 hours. After the addition is complete, the reaction is carried out for 2-3 hours to obtain the core emulsion.
[0010] Furthermore, caprolactone-modified acrylic acid and styrene mixed monomers and initiator solution are simultaneously added dropwise to the core layer emulsion, and microencapsulated repair agent is added at the same time. The dropwise addition time is 1-2 hours, and after the dropwise addition is completed, the mixture is stirred at 75-85℃ for 2-3 hours.
[0011] Furthermore, fluorinated acrylate, light inhibitor, KH570 modified nano-silica mixed monomer, initiator solution and emulsifier are added dropwise to the emulsion encapsulated in the intermediate layer over a period of 1-2 hours. After the addition is complete, the mixture is kept at 75-85°C for 2-3 hours for further reaction.
[0012] Further, the shell-layer polymer emulsion is cooled to 45-55°C, an emulsifier is added and reacted for 35-45 minutes, the pH is adjusted to 7-8 with ammonia, and the material is filtered to obtain a core-shell structured acrylic emulsion.
[0013] Furthermore, after the core layer mixed monomers are emulsified, the temperature is raised to 80-82℃ and the initiator solution is added dropwise. The dropping rate is controlled to be 50%-60% of the total initiator solution added per hour to ensure uniform monomer polymerization.
[0014] Furthermore, the addition rate of the microencapsulated repair agent is consistent with the dropping rate of the mixed monomers of fluorinated acrylate, photoinhibitor and KH570 modified nano-silica, and the stirring speed is controlled at 200-300 r / min to avoid microcapsule aggregation or rupture.
[0015] On the other hand, the present invention also provides an application of a waterborne acrylic topcoat based on a core-shell structure design. The above-mentioned waterborne acrylic topcoat based on a core-shell structure design is used in the fields of coating of battery pack shells for new energy vehicles, coating of high-end engineering machinery, coating of outdoor steel structure buildings and facilities, and coating of marine platforms.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention innovatively introduces microcapsules with urea-formaldehyde resin as the wall material and isocyanate compound as the core material into the core layer, successfully endowing the coating with intelligent self-healing ability. When the coating develops microcracks due to external stress, the stress at the crack tip will cause the microcapsules to rupture, and the released repair agent will immediately react with the moisture / active groups reserved in the environment or in the formula to generate substances such as polyurea, thereby automatically and efficiently filling and healing the cracks. This invention, through its unique triple structure design of "rigid core - flexible intermediate layer - functional shell", perfectly coordinates the high hardness, high flexibility and excellent adhesion of the coating, overcoming the technical contradiction that traditional coatings cannot achieve both high hardness and high flexibility. This allows the coating to maintain excellent adhesion, impact resistance and crack resistance under different temperature environments (especially low temperatures). Detailed Implementation
[0017] The technical solutions in the embodiments will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection.
[0018] This invention provides a water-based acrylic topcoat based on a core-shell structure design. The water-based acrylic topcoat comprises a water-based acrylic emulsion, which includes a core layer, an intermediate layer, a shell layer, additives, and the remainder water. The components, by mass, include: Core layer: 20-30 parts methyl methacrylate, 10-20 parts butyl acrylate, 3-7 parts hydroxyethyl acrylate, and 2-4 parts vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 8-12 parts caprolactone-modified acrylic acid, 6-10 parts styrene, and 4-6 parts microencapsulated repair agent; Shell: 10-14 parts of fluorinated acrylate, 0.3-0.7 parts of light inhibitor and 1-3 parts of KH570 modified nano-silica; Additives: 1-2 parts emulsifier, 0.4-0.8 parts potassium persulfate, and ammonia water; The ammonia solution is used to adjust the pH of the topcoat to 7-8. The microencapsulated repair agent uses urea-formaldehyde resin as the wall material and encapsulates isocyanate compounds as the repair agent.
[0019] In a further embodiment of this example, the particle size of the microencapsulated repair agent is 1-5 μm, and the emulsifier includes the reactive emulsifier COPS-1.
[0020] It should be noted that the core layer uses a combination of rigid monomers, namely methyl methacrylate and butyl acrylate, and introduces reactive phosphoramide flame retardant monomers to provide the coating with basic mechanical and flame retardant properties.
[0021] The intermediate layer incorporates caprolactone-modified acrylic acid and microencapsulated repair agents to significantly reduce the glass transition temperature and improve low-temperature flexibility. When the coating is damaged, the microcapsules rupture to release the repair agent, which reacts with moisture in the environment to generate polyurea to repair the cracks.
[0022] The shell layer uses fluorinated acrylate to provide durable weather resistance, excellent hydrophobicity and light inhibitory properties, and adds KH570 modified nano-silica to improve coating hardness, wear resistance and synergistic flame retardancy, giving the coating excellent surface properties.
[0023] On the other hand, embodiments of the present invention also provide a method for preparing a water-based acrylic topcoat based on a core-shell structure design, comprising the following steps: Deionized water, emulsifier and methacrylic acid were added to the reaction vessel, heated and stirred, and then methyl methacrylate, butyl acrylate, hydroxyethyl acrylate and vinyltriphenyl dipentyl glycol phosphoramide mixed monomers were added for emulsification and then heated again. Potassium persulfate initiator solution was added dropwise to react and obtain core layer emulsion. A mixture of caprolactone-modified acrylic acid and styrene monomers and an initiator solution were simultaneously added dropwise to the core layer emulsion, and a microencapsulated repair agent was added slowly at the same time. After the addition was completed, the reaction was stirred to obtain an emulsion with an intermediate layer. Fluorinated acrylate, light inhibitor and KH570 modified nano-silica mixed monomer, initiator solution and emulsifier are added dropwise to the emulsion wrapped in the intermediate layer. After the addition is completed, the reaction is completed to obtain the shell-layer polymerized emulsion. After adding emulsifier and reacting, the pH is adjusted to 7-8 with ammonia water, and then filtered to obtain a core-shell structured aqueous acrylic emulsion. The core-shell structured waterborne acrylic emulsion is mixed and dispersed with pigments, fillers, thickeners, and defoamers to obtain a waterborne acrylic topcoat.
[0024] In a further embodiment of this example, deionized water, reactive emulsifier COPS-1, and methacrylic acid are added to a reaction vessel, heated to 60-65°C, and stirred for 35-45 minutes. A mixture of methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentyl glycol phosphoramide monomers is added and emulsified for 30-40 minutes. The temperature is then raised to 80-85°C, and potassium persulfate initiator solution is added dropwise over 1-2 hours. After the addition is complete, the reaction is carried out for 2-3 hours to obtain a core layer emulsion.
[0025] In a further embodiment of this example, caprolactone-modified acrylic acid and styrene mixed monomers and an initiator solution are simultaneously added dropwise to the core layer emulsion, and a microencapsulated repair agent is added at the same time. The dropwise addition takes 1-2 hours, and after the dropwise addition is completed, the mixture is stirred at 75-85°C for 2-3 hours.
[0026] In a further embodiment of this example, fluorinated acrylate, light inhibitor, KH570 modified nano-silica mixed monomer, initiator solution and emulsifier are added dropwise to the emulsion encapsulated by the intermediate layer over a period of 1-2 hours. After the addition is complete, the mixture is kept at 75-85°C for 2-3 hours for reaction.
[0027] In a further embodiment of this example, the shell polymer emulsion is cooled to 45-55°C, an emulsifier is added and reacted for 35-45 minutes, the pH is adjusted to 7-8 with ammonia, and the material is filtered to obtain a core-shell structured acrylic emulsion.
[0028] In a further embodiment of this example, after the core layer mixed monomers are emulsified, the temperature is raised to 80-82°C and the initiator solution is added dropwise. The dropping rate is controlled to be 50%-60% of the total initiator solution added per hour to ensure uniform monomer polymerization.
[0029] In a further embodiment of this example, the addition rate of the microencapsulated repair agent is consistent with the dropping rate of the mixed monomers of fluorinated acrylate, photoinhibitor and KH570 modified nano-silica, and the stirring speed is controlled at 200-300 r / min to avoid microcapsule aggregation or rupture.
[0030] It should be noted that: a microencapsulated repair agent was added simultaneously during the intermediate layer polymerization stage, and the process parameters were optimized to ensure that the microcapsules remained intact and were uniformly dispersed in the polymer emulsion during the polymerization process. Fluorinated acrylate was introduced as a shell monomer, and the durability and functionality of the shell were enhanced by grafting modified nano-silica.
[0031] On the other hand, embodiments of the present invention also provide an application of a waterborne acrylic topcoat based on a core-shell structure design. The above-mentioned waterborne acrylic topcoat based on a core-shell structure design is applied in the fields of coating of battery pack shells for new energy vehicles, coating of high-end engineering machinery, coating of outdoor steel structure buildings and facilities, and coating of marine platforms.
[0032] Example 1
[0033] The mass fractions of each component are as follows: Core layer: 25 parts methyl methacrylate, 15 parts butyl acrylate, 5 parts hydroxyethyl acrylate, and 3 parts vinyltriphenyl dipentyl glycol phosphoramide; Intermediate layer: 10 parts caprolactone-modified acrylic acid, 8 parts styrene, and 5 parts microencapsulated repair agent; Shell: 12 parts fluorinated acrylate, 0.5 parts light inhibitor and 2 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0034] Deionized water, reactive emulsifier COPS-1, and methacrylic acid were added to a reaction vessel, heated to 60°C, and stirred for 40 minutes. A mixture of methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentylene glycol phosphoramide monomers was then added and emulsified for 35 minutes. The temperature was then raised to 80°C, and potassium persulfate initiator solution was added dropwise over 2 hours. After the addition was complete, the reaction was carried out for 3 hours to obtain a core layer emulsion. The core layer mixed monomers, namely methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentylene glycol phosphoramide, were emulsified. After the emulsification was complete, the temperature was raised to 80°C, and the initiator solution was added dropwise. The dropwise rate was controlled to be 50% of the total initiator solution volume per hour to ensure uniform monomer polymerization.
[0035] A mixture of caprolactone-modified acrylic acid and styrene monomers and an initiator solution were simultaneously added dropwise to the core emulsion, along with a microencapsulated repair agent. The dropwise addition time was 1.5 hours, and after the addition was complete, the mixture was stirred at 80°C for 2.5 hours. The addition rate of the microencapsulated repair agent was consistent with the dropwise acceleration rate of the mixture of fluorinated acrylate, light inhibitor, and KH570-modified nano-silica monomers, and the stirring speed was controlled at 250 r / min to avoid microcapsule aggregation or rupture.
[0036] Fluorinated acrylate, light inhibitor, KH570 modified nano-silica mixed monomer, initiator solution and emulsifier were added dropwise to the emulsion encapsulated in the intermediate layer over a period of 2 hours. After the addition was completed, the mixture was kept at 80°C for 3 hours.
[0037] The shell-layer polymer emulsion was cooled to 50°C, an emulsifier was added and reacted for 40 minutes. The pH was adjusted to 8 with ammonia, and the product was filtered to obtain a core-shell structured acrylic emulsion.
[0038] Example 2
[0039] The difference from Example 1 is that the mass parts of each component are as follows: core layer: 28 parts methyl methacrylate, 12 parts butyl acrylate, 6 parts hydroxyethyl acrylate and 3.5 parts vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 9 parts caprolactone-modified acrylic acid, 9 parts styrene, and 4.5 parts microencapsulated repair agent; Shell: 11 parts fluorinated acrylate, 0.6 parts light inhibitor and 2.5 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0040] Example 3
[0041] The difference from Example 1 is that the mass parts of each component are as follows: core layer: 25 parts of methyl methacrylate, 15 parts of butyl acrylate, 5 parts of hydroxyethyl acrylate and 3 parts of vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 12 parts caprolactone-modified acrylic acid, 7 parts styrene, and 5.5 parts microencapsulated repair agent; Shell: 12 parts fluorinated acrylate, 0.5 parts light inhibitor and 2 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0042] Example 4
[0043] The difference from Example 1 is that the mass parts of each component are as follows: core layer: 25 parts of methyl methacrylate, 15 parts of butyl acrylate, 5 parts of hydroxyethyl acrylate and 3 parts of vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 10 parts caprolactone-modified acrylic acid, 8 parts styrene, and 5 parts microencapsulated repair agent; Shell: 14 parts fluorinated acrylate, 0.7 parts light inhibitor and 3 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0044] Example 5
[0045] The difference from Example 1 is that the mass parts of each component are as follows: core layer: 25 parts of methyl methacrylate, 15 parts of butyl acrylate, 5 parts of hydroxyethyl acrylate and 3 parts of vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 6 parts caprolactone-modified acrylic acid, 9 parts styrene, and 8 parts microencapsulated repair agent; Shell: 12 parts fluorinated acrylate, 0.5 parts light inhibitor and 2 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0046] Example 6
[0047] The difference from Example 1 is that the mass parts of each component are as follows: core layer: 25 parts of methyl methacrylate, 15 parts of butyl acrylate, 5 parts of hydroxyethyl acrylate and 3 parts of vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 10 parts caprolactone-modified acrylic acid, 8 parts styrene, and 5 parts microencapsulated repair agent; Shell: 12 parts fluorinated acrylate, 0.5 parts light inhibitor and 2 parts KH570 modified nano-silica; Additives: 1.8 parts emulsifier, 0.5 parts potassium persulfate, and 100 parts deionized water.
[0048] Comparative Example 1 The mass fractions of each component are as follows: Core layer: 25 parts methyl methacrylate, 15 parts butyl acrylate, 5 parts hydroxyethyl acrylate, and 3 parts vinyltriphenyl dipentyl glycol phosphoramide; Shell: 12 parts fluorinated acrylate, 0.5 parts light inhibitor and 2 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0049] Deionized water, reactive emulsifier COPS-1, and methacrylic acid were added to a reaction vessel, heated to 60°C, and stirred for 40 minutes. A mixture of methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentylene glycol phosphoramide monomers was then added and emulsified for 35 minutes. The temperature was then raised to 80°C, and potassium persulfate initiator solution was added dropwise over 2 hours. After the addition was complete, the reaction was carried out for 3 hours to obtain a core layer emulsion. The core layer mixed monomers, namely methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentylene glycol phosphoramide, were emulsified. After the emulsification was complete, the temperature was raised to 80°C, and the initiator solution was added dropwise. The dropwise rate was controlled to be 50% of the total initiator solution volume per hour to ensure uniform monomer polymerization.
[0050] Fluorinated acrylate, light inhibitor, KH570 modified nano-silica mixed monomer, initiator solution and emulsifier were added dropwise to the emulsion over 2 hours. After the addition was completed, the mixture was kept at 80°C for 3 hours.
[0051] The shell-layer polymer emulsion was cooled to 50°C, an emulsifier was added and reacted for 40 minutes. The pH was adjusted to 8 with ammonia, and the product was filtered to obtain a core-shell structured acrylic emulsion.
[0052] Comparative Example 2 The difference from Example 1 is that the mass parts of each component are as follows: core layer: 25 parts of methyl methacrylate, 15 parts of butyl acrylate and 5 parts of hydroxyethyl acrylate; Intermediate layer: 10 parts caprolactone-modified acrylic acid, 8 parts styrene, and 5 parts microencapsulated repair agent; Shell: 12 parts fluorinated acrylate, 0.5 parts light inhibitor and 2 parts KH570 modified nano-silica; Additives: 1.5 parts emulsifier, 0.6 parts potassium persulfate, and 100 parts deionized water.
[0053] The waterborne acrylic emulsions prepared in Examples 1-6 and Comparative Examples 1 and 2 were used to prepare waterborne acrylic topcoats. The preparation method of waterborne acrylic is as follows: Add 3g of deionized water, 0.8g of Disperbyk®-190 dispersant, 0.2g of Hydropalat® 436 wetting agent, and 0.3g of BYK®-024 defoamer to the dispersion tank in sequence; stir at 300-500 rpm for 5 minutes to ensure thorough mixing.
[0054] Slowly add 12g of titanium dioxide R-706, being careful not to generate dust. After adding the powder, increase the speed to 800-1000 rpm and stir for 10 minutes to completely wet the powder, resulting in a thick slurry without any dry powder.
[0055] Then increase the rotation speed to 1500-2000 rpm and disperse at high speed for 20-30 minutes. Use a scraper fineness meter to check the fineness of the slurry. When the fineness is ≤15μm, stop the dispersion. Reduce the rotation speed, add 0.1g of Acticide® MBS preservative, and stir for another 5 minutes to obtain a uniform and fine white slurry, which can be used as the first slurry for later use.
[0056] Add 70g of the aqueous acrylic emulsion prepared in the examples or comparative examples to the paint mixing tank. While stirring at a low speed of 300-500rpm, first slowly add 1.5g of Texanol™ film-forming aid and stir for 10 minutes to fully mix it. Then, add 0.2g of BYK®-346 leveling agent, 0.5g of Raybo® 60 corrosion inhibitor, 0.2g of BYK®-024 defoamer and 5g of deionized water in sequence to obtain the emulsion mixture.
[0057] Slowly add the first color paste to the emulsion mixture. After adding all the paste, continue stirring for 15-20 minutes to ensure the system is completely homogeneous. Pre-dilute 0.4g of UH-752 thickener with some deionized water, and then slowly add it to the paint while stirring at low speed to avoid localized thickening. Slowly add ammonia water to adjust the pH of the system to 8.0-9.0. Continue stirring until the system is homogeneous. Stop stirring and then filter the paint through a 100-200 mesh filter to remove any possible gel particles or impurities. Package and store the paint for 24 hours to cure.
[0058] The topcoats prepared from the products obtained in Examples 1-6 and Comparative Examples 1 and 2 were tested for self-healing efficiency, pencil hardness, low-temperature flexibility, flame retardancy, and weather resistance. The self-healing efficiency was tested according to GB / T37267-2018 Self-Healing Coatings; the pencil hardness was tested according to GB / T 6739-2022 Paints and Varnishes Pencil Method for Determining Film Hardness; the low-temperature flexibility was tested according to GB / T 6742-2021 Paints and Varnishes Bending Test (Cylindrical Shaft); the flame retardancy was tested according to UL 94-2024 Burning Test of Plastic Materials for Equipment and Appliance Components; and the weather resistance was tested according to GB / T 1865-2009 Paints and Varnishes Artificial Climate Aging and Artificial Radiation Exposure (Filtered Xenon Arc Radiation). The test results are shown in Table 1 below.
[0059] Table 1
[0060] In summary, all embodiments of the present invention meet the requirements of 85%-95% self-healing efficiency, pencil hardness H and above, no low-temperature cracking at -30℃, flame retardant UL94 V-0 rating, and gloss retention rate of over 80% after 1000 hours of weathering. They fully meet the requirements of harsh environments such as high temperature, high humidity, and strong corrosion. Adjusting key components can optimize performance in a targeted manner. For example, the upper limit of microcapsules in Embodiment 5 leads to the highest self-healing performance; the upper limit of fluorinated monomers in Embodiment 4 leads to the best weather resistance.
[0061] Comparative Example 1, lacking microcapsules, saw its self-repair efficiency plummet to 5%, directly demonstrating that microencapsulated repair agents are a necessary condition for achieving self-repair function. Comparative Example 2, lacking reactive flame-retardant monomers, saw its flame retardant rating drop from V-0 to V-2, proving the key role of reactive phosphoramide monomers in long-lasting flame retardancy, and that additive flame retardants in existing technologies cannot replace their effect.
[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A water-based acrylic topcoat based on a core-shell structure design, characterized in that, The water-based acrylic topcoat comprises a water-based acrylic emulsion, which includes a core layer, an intermediate layer, a shell layer, additives, and the remainder water. Each component, by mass, comprises: Core layer: 20-30 parts methyl methacrylate, 10-20 parts butyl acrylate, 3-7 parts hydroxyethyl acrylate, and 2-4 parts vinyltriphenyl dinepentyl glycol phosphoramide; Intermediate layer: 8-12 parts caprolactone-modified acrylic acid, 6-10 parts styrene, and 4-6 parts microencapsulated repair agent; Shell: 10-14 parts of fluorinated acrylate, 0.3-0.7 parts of light inhibitor and 1-3 parts of KH570 modified nano-silica; Additives: 1-2 parts emulsifier, 0.4-0.8 parts potassium persulfate, and ammonia water; The ammonia solution is used to adjust the pH of the topcoat to 7-8. The microencapsulated repair agent uses urea-formaldehyde resin as the wall material and encapsulates isocyanate compounds as the repair agent.
2. The water-based acrylic topcoat based on a core-shell structure design according to claim 1, characterized in that, The microencapsulated repair agent has a particle size of 1-5 μm, and the emulsifier includes the reactive emulsifier COPS-1.
3. A method for preparing a waterborne acrylic topcoat based on a core-shell structure design according to any one of claims 1-2, characterized in that, Includes the following steps: Deionized water, emulsifier and methacrylic acid were added to the reaction vessel, heated and stirred, and then methyl methacrylate, butyl acrylate, hydroxyethyl acrylate and vinyltriphenyl dipentyl glycol phosphoramide mixed monomers were added for emulsification and then heated again. Potassium persulfate initiator solution was added dropwise to react and obtain core layer emulsion. A mixture of caprolactone-modified acrylic acid and styrene monomers and an initiator solution were simultaneously added dropwise to the core layer emulsion, and a microencapsulated repair agent was added slowly at the same time. After the addition was completed, the reaction was stirred to obtain an emulsion with an intermediate layer. Fluorinated acrylate, light inhibitor and KH570 modified nano-silica mixed monomer, initiator solution and emulsifier are added dropwise to the emulsion wrapped in the intermediate layer. After the addition is completed, the reaction is completed to obtain the shell-layer polymerized emulsion. After adding emulsifier and reacting, the pH is adjusted to 7-8 with ammonia water, and then filtered to obtain a core-shell structured aqueous acrylic emulsion. The core-shell structured waterborne acrylic emulsion is mixed and dispersed with pigments, fillers, thickeners, and defoamers to obtain a waterborne acrylic topcoat.
4. The method for preparing waterborne acrylic topcoat based on core-shell structure design according to claim 3, characterized in that, Deionized water, reactive emulsifier COPS-1, and methacrylic acid were added to a reaction vessel, heated to 60-65°C, and stirred for 35-45 minutes. Methyl methacrylate, butyl acrylate, hydroxyethyl acrylate, and vinyltriphenyl dipentyl glycol phosphoramide mixed monomers were added and emulsified for 30-40 minutes. The temperature was then raised to 80-85°C, and potassium persulfate initiator solution was added dropwise over 1-2 hours. After the addition was complete, the reaction was carried out for 2-3 hours to obtain a core emulsion.
5. The method for preparing waterborne acrylic topcoat based on core-shell structure design according to claim 3, characterized in that, A solution of caprolactone-modified acrylic acid and styrene monomers and an initiator was simultaneously added to the core layer emulsion, along with a microencapsulated repair agent. The addition time was 1-2 hours, and after the addition was completed, the mixture was stirred at 75-85°C for 2-3 hours.
6. The method for preparing waterborne acrylic topcoat based on core-shell structure design according to claim 3, characterized in that, Fluorinated acrylate, light inhibitor, KH570 modified nano-silica mixed monomer, initiator solution and emulsifier are added dropwise to the emulsion encapsulated in the intermediate layer over 1-2 hours. After the addition is complete, the mixture is kept at 75-85℃ for 2-3 hours.
7. The method for preparing waterborne acrylic topcoat based on core-shell structure design according to claim 3, characterized in that, The shell-layer polymer emulsion is cooled to 45-55°C, an emulsifier is added and reacted for 35-45 minutes. The pH is adjusted to 7-8 with ammonia water, and the product is filtered to obtain a core-shell structured acrylic emulsion.
8. The method for preparing waterborne acrylic topcoat based on core-shell structure design according to claim 3, characterized in that, After the core layer mixed monomers are emulsified, the temperature is raised to 80-82℃ and the initiator solution is added dropwise. The dropping rate is controlled to be 50%-60% of the total initiator solution per hour to ensure uniform monomer polymerization.
9. The method for preparing a waterborne acrylic topcoat based on a core-shell structure design according to claim 3, characterized in that, The addition rate of the microencapsulated repair agent is consistent with the dropping rate of the mixed monomers of fluorinated acrylate, photoinhibitor and KH570 modified nano-silica, and the stirring speed is controlled at 200-300 r / min to avoid microcapsule aggregation or rupture.
10. An application of a water-based acrylic topcoat based on a core-shell structure design, characterized in that, The application of the waterborne acrylic topcoat based on the core-shell structure design according to any one of claims 1-2 in the fields of coating of battery pack shells for new energy vehicles, coating of high-end engineering machinery, coating of outdoor steel structure buildings and facilities, and coating of marine platforms.
Citation Information
Patent Citations
Preparation method of phase transformation material microcupsule
CN101045857A
High-solid content environment-friendly phase transition microcapsule and preparation method thereof
CN104592434A
Acrylate emulsion with core-shell structure and preparation method thereof
CN115124657A
Preparation method of water-based acrylic resin coating containing core-shell structure nanoparticles
CN118359971A
Double-shell self-repairing microcapsule, and preparation method therefor and use thereof
WO2022011814A1